Mixed Synchronization of Chaotic Financial Systems by Using Linear Feedback Control - Ke Ding; Xing Xu (Discrete Dynamics in Nature and Society)
This paper deals with the mixed synchronization (coexistence of synchronization and antisynchronization) of two chaotic financial systems. Two mixed synchronization criteria for two chaotic financial systems are derived with a single controller and without external controls, respectively. In addition, the control method and synchronization criteria are applied to study the mixed synchronization of a class of modified chaotic financial systems. Three examples are used to illustrate the effectiveness of our derived results.